AN ANALYSIS OF PSYCHOANALYTIC DYNAMICS IN SYLVIA PLATH'S POEM LADY LAZARUS - Rheisa Nurfariza Zachra; Tarina Roliani; Thesa Izfadllillah (ReALL - Research on Applied Linguistics and Literature, 2024)
This study analyzes the character Lady Lazarus in Sylvia Plath's poem against the backdrop of widespread emotional stress among young people, which often leads to depression and anxiety. Through a descriptive qualitative approach, this research examines the id, ego, and superego, as well as the techniques of condensation, displacement, and symbolization in the poem using Freud's theory. The results show that Lady Lazarus is dominated by the death drive (id), balances it with reality (ego), and rebels against social norms (superego). Additionally, the analysis of condensation, displacement, and symbolization in Lady Lazarus reveals that metaphors are used to convey complex psychological conflicts, particularly the struggle between life and death, objectification, and the desire for renewal and self-destruction, in line with Freud’s theory. These techniques uncover complex inner conflicts and represent the loss of humanity in the struggle between life and death.